Densification of surface-modified silicon carbide powder by spark-plasma-sintering. Issue 15 (December 2021) - Montón, Alejandro; Maury, Francis; Chevallier, Geoffroy; Estournès, Claude; Ferrato, Marc; Grossin, David
Highlights: Innovative grafting of monomer-derived SiC ceramic. Enhancing the sintering behavior by SPS of SiC powder by surface functionalization. Significant improvement of the final SiC part density. Abstract: SiC was densified by spark plasma sintering (SPS) and the effects of surface modification of the powder particles on its sintering behavior were investigated. The pressure and temperature conditions were set to 50 MPa and 2200 °C, respectively. Specific SPS experiments at a lower temperature ( i.e. 1600 °C) was performed to analyze the efficiency of the sintering and the early stage of the densification in softer conditions. The surface functionalization was carried out by grafting a thin molecular layer of a preceramic precursor on the grain surface of SiC particles, which acts as a sintering additive without producing contamination by heteroatoms since, in addition to hydrogen, it contained only Si and C in the same ratio 1:1 as silicon carbide. One of the advantages of this surface functionalization is that it reduces the temperature at which the sintering process begins and therefore it facilitates and increases the densification of the final SiC parts.